2001
DOI: 10.1099/0022-1317-82-5-1215
|View full text |Cite
|
Sign up to set email alerts
|

Genetic heterogeneity among parapoxviruses isolated from sheep, cattle and Japanese serows (Capricornis crispus)

Abstract: Standard strains of four parapoxviruses and seven unclassified Japanese strains isolated from sheep, cattle and wild Japanese serows (Capricornis crispus) were compared molecularly. Restriction fragment length polymorphism (RFLP) analysis of viral DNA, indirect immunofluorescence assays using monoclonal antibodies, partial nucleotide sequencing of the envelope gene, phylogenetic analysis and PCR-RFLP were carried out. These analyses revealed that the parapoxviruses were divided into four groups and the region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
58
1
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 28 publications
2
58
1
1
Order By: Relevance
“…The clinical signs of CE is the first diagnostic tool in the field. Techniques such as cell culture [19,26,28] and PCR have been used for virus isolation and detection [9,14,15,19,26,28]. PCR was evaluated as a fast, cheap and valid technique for virus detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical signs of CE is the first diagnostic tool in the field. Techniques such as cell culture [19,26,28] and PCR have been used for virus isolation and detection [9,14,15,19,26,28]. PCR was evaluated as a fast, cheap and valid technique for virus detection.…”
Section: Introductionmentioning
confidence: 99%
“…PCR was evaluated as a fast, cheap and valid technique for virus detection. The most common genes used are B2L gene; a highly immunogenic envelope gene [19,26,28] and Orf F1L gene; an immunodominant gene [1,9,12,14,15,18,19,26,28].…”
Section: Introductionmentioning
confidence: 99%
“…Restriction fragment length polymorphism (RFLP) and cross-hybridization of viral DNA are also used 15 . We have previously demonstrated that phylogenetic analysis of partial sequences of the viral envelope gene and polymerase chain reaction (PCR)-RFLP are useful for the differentiation of parapoxviruses 6 . Recent genetic studies suggest that seal poxvirus (SPV) should be included in the genus Parapoxvirus 1 but squirrel poxvirus may be classified into a different genus although the morphological features observed by electron microscopy are the same as for parapoxvirus 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Some ORFVs were isolated from cases of bovine papular stomatitis in cattle and some BPSVs were isolated from sheep 15 . Moreover, both ORFV and BPSV cause pustular dermatitis in Japanese serows (Capricornis crispus) 6,7 and both ORFV and PCPV also cause papular stomatitis in Finnish reindeer (Rangifer tarandus tarandus) 19 . In addition, experimental transmission of parapoxvirus from the Japanese serow to sheep, goats and cattle has succeeded 11,13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…Although parapoxvirus infections in Japanese serows are mainly caused by ORFVs 3 , as mentioned above, ORFVs can infect cattle, and experimental infection from Japanese serow to cattle was successful 7 . On the other hand, a BPSV Ishikawa-S strain was previously isolated from a Japanese serow, not a cow, in Ishikawa Prefecture 2,14 . These findings indicate the possibility that the virus cycles between cattle and Japanese serows and that the spread of parapoxvirus infections in cattle is correlated with the expanding range of the Japanese serows.…”
Section: Introductionmentioning
confidence: 99%